Fugitives from France: Huguenot refugees, revolutionary émigrés, and the origins of modern exile - Summers, Kelly (My University, 2023)
Attempts to ban emigration from France in the 1680s, and again in the 1790s, failed, spawning two categories of exile that have more in common than is typically acknowledged. Huguenot refugees who fled Louis XIV’s Catholicization campaign tend to be viewed as the last religious exiles of the early modern era, whereas émigrés who left in the wake of 1789 are seen as exemplars of a new type of political exile born of revolution. In fact, a comparison reveals their shared origins in the conflict between a centralizing state intent on policing its populace’s beliefs and movements and the global reverberations of the Protestant Reformation and French Revolution, respectively. Both diasporas included a conspicuous subset who fought France in league with its foreign enemies, as well as an unarmed majority fleeing threats to their freedom of conscience, property, and at times, very lives. After tracing the evolution of such freighted terms as fugitive, refugee, rebel, deserter, and émigré, the chapter concludes by examining how France’s two great migrations were juxtaposed in revolutionary debates over the right to leave and return to one’s country, which partially explains their divergent treatment by historians.
Keywords: Huguenots; revolutionary émigrés; France